Efektivitas Logoterapi Medical Ministry terhadap Kebermaknaan Hidup pada Warga Binaan dengan HIV/AIDS - Widiyastuty, Riesma; Wangi, Eneng Nurlaili; Fahmi, Irfan (Universitas Muria Kudus, 2023)
This research aims to determine the effectiveness of logotherapy medical ministry on the level of meaning in life among five inmates with HIV/AIDS. Participants are guided to understand the inevitable tragic experiences through the ability to take a stance and undergo a self-transcendence process, which is a distinctive feature of medical ministry compared to other logotherapy techniques. It focuses on understanding and evaluating the